Bibliometric analysis of peer-reviewed literature on antimicrobial stewardship from 1990 to 2019 - Waleed M. Sweileh (BMC, 2021)
Abstract Background The World Health Organization recommended the implementation of antimicrobial stewardship (AMS) in the clinical settings to minimize the development and spread of antimicrobial resistance (AMR). The current study aimed to assess global research activity on AMS as one measure for efforts dedicated to contain AMR. Method A bibliometric method was applied using Scopus. A validated search query was implemented. Bibliometric indicators and mapping were generated. The study period was from 1990 to 2019. The search query utilized the keywords "antimicrobial stewardship" or "antibiotic stewardship" in the titles or abstracts. In addition, documents with the term "restrict" or "restriction" if used with the terms "antimicrobial" or "antibiotic" were retrieved. Results The search query returned 4402 documents. The keyword "antimicrobial stewardship" returned 2849 documents while the keyword "antibiotic stewardship" returned 1718 documents. The terms restrict/restriction and antimicrobial/antibiotics returned 209 documents. The number of publications and cumulative citations showed a steep and parallel increase in the last decade. The region of the Americas returned the most while the Eastern Mediterranean region returned the least. The United States (n = 1834, 41.7%) ranked first. Main research themes in the retrieved literature were the (1) impact of AMS on hospital length stay, (2) role of pharmacists, and (3) development of resistance of various pathogens. Clostridium difficile (n = 94) and Staphylococcus aureus (n = 76) were among the most frequently encountered author keywords. The Infection Control and Hospital Epidemiology journal ranked first (n = 245, 5.6%, h-index = 134) while documents published in the Clinical Infectious Diseases journal (h-index = 321) received the highest number of citations per document (70.7). At the institutional level, the US Centers for Disease Prevention and Control (n = 93, 2.1%) ranked first followed by the Imperial College London (n = 86, 2.0%). The main funding sponsors were the National Institute of Health. Pfizer, Merck, and Bayer pharmaceutical companies played a key role in funding AMS research. International research collaboration between developed (n = 3693, 83.9%) and developing countries (n = 759, 17.2%). Conclusion The fight against AMR is a global responsibility and implementation of AMS need to be carried out across the globe. International research collaboration between developing and developed countries should be encouraged.